Norwegian police law, crime prevention and its (need for more) democratic legitimacy - Nilsen, John Reidar (Bergen Journal of Criminal Law & Criminal Justice, 2022)
The article questions the democratic legitimacy of parts of contemporary Norwegian police law. The analysis focuses on the historical background of the Police Act, the lack of precise regulation of the police’s competences in general and lack of precise preventive work, to argue that the ideal of democratic legitimacy is not met in contemporary Norwegian police law.